2021
DOI: 10.3892/mmr.2021.12292
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of taurine on sepsis‑induced lung injury via inhibiting the p38/MAPK signaling pathway

Abstract: Sepsis, a leading cause of acute lung injury (ALI), is characterized by an overwhelming systemic inflammatory response and widespread organ injury, particularly in the lungs. Taurine, an intracellular free amino acid, has been used for the treatment of various diseases, including lung injury; however, the underlying mechanisms are unclear. The present study aimed to investigate the protective effect of taurine on septic ALI and the underlying mechanism. A septic ALI model was established by performing cecal li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…MAPKs signaling has been shown to be essential for dysregulated and overly aggressive inflammatory response in the development of sepsis. 24 MAPKs were abnormally activated in rats with sepsis-associated acute lung injury, 25 and inhibition in the phosphorylation of p38 and JNK in lung tissues alleviated sepsis-associated acute lung injury. 24 Activation of CXCLs/CXCR2 axis promoted the activation of p38/ERK signaling to regulate cell survival and migration in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 94%
“…MAPKs signaling has been shown to be essential for dysregulated and overly aggressive inflammatory response in the development of sepsis. 24 MAPKs were abnormally activated in rats with sepsis-associated acute lung injury, 25 and inhibition in the phosphorylation of p38 and JNK in lung tissues alleviated sepsis-associated acute lung injury. 24 Activation of CXCLs/CXCR2 axis promoted the activation of p38/ERK signaling to regulate cell survival and migration in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Taurine has been demonstrated to inhibit the lung damage caused by oxidative stress by enhancing the activity of antioxidWWant enzymes in the lung ( Schuller-Levis et al, 1994 ; Abdih et al, 2000 ; Zhao et al, 2018 ). Chen and colleagues discovered that taurine can attenuate sepsis-induced lung injury through anti-inflammatory actions and antioxidative stress, reducing overexpression of tumor necrosis factor (TNF)-α and IL-1β and neutrophil infiltration ( Chen, J. et al, 2021 ). Early studies also showed that abnormalities of the taurine metabolism of occurred in viral pneumonia and lipopolysaccharide-induced pulmonary injury ( Chen, F. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…51 In addition, lidocaine has a protective effect on LPS-induced acute lung injury (ALI) in rats by inhibiting an excessive inflammatory response. 52 In this study, we explored the effect of lidocaine on intestinal barrier function in WAS-induced IBS rats, a widely used model for evaluating drugs targeting intestinal barrier injury. 34 Lidocaine treatment effectively ameliorated IBS-related symptoms in rats, including visceral hypersensitivity, body weight changes, low-level inflammation, and alterations in spleen and thymus index.…”
Section: Discussionmentioning
confidence: 99%